دور المشروعـات المصغـرة في تحقيق ريادة الأعمال في الجزائــر - بودرامـة, مصطفى (Sciences humaines; Vol. 24 (2012): SCIENCES HUMAINES)
تهدف هذه الدراسة إلى توضيح مفهوم المشروعات المصغرة وبيان أهميتها ودورها في تحقيق ريادة الأعمال في الجزائر، وتنبع أهمية الدراسة من ضرورة تفعيل دور المشروعات المصغرة في ظل متغيرات العولمة وخاصة التقليل من حدة تأثير الأزمة المالية العالمية على الاقتصاد الجزائري، إضافة إلى تركيز البحث على أهم المشاكل التي تواجه تطورها حتى تصبح ريادية وتضمن ديمومتها. وفي ختام الدراسة أوصى الباحث بعدد من التوصيات منها ضرورة تأهيلها وتأهيل        This study aims to clarify the concept of mini-projects and indicate the importance and role in the investigation of entrepreneurship in Algeria.     The importance of the study is activating the role of micro-projects under the variables of globalization, in particularly the global financial crisis and its impact on the economies of developing countries, as well as to focus research on the most important problems facing their development of mini-projects to become a pilot and to ensure durability.     Finally the study is concluded by providing some recommendations such as the need for rehabilitation and the rehabilitation of its environment.